Trichoscopy in Unveiling the Triad of Netherton Syndrome - H Bangaru; D Ashwini (Clinical Dermatology Review)
Netherton syndrome (NS) is a rare autosomal recessive disorder characterized by the triad of congenital ichthyosiform erythroderma or ichthyosis linearis circumflexa (ILC), hair shaft abnormalities, and atopic diathesis (elevated serum IgE) caused by mutations in serine protease-inhibitor (SPINK5) gene located on chromosome 5q31–32. Here, we present a case of a 16-year-old female born to second-degree consanguineous marriage who presented with a history of atopy, generalized xerosis, plaques with serpiginous borders, and double-edged scales over the trunk, upper and lower limbs, lichenification in flexures, sparse eyelashes, and eyebrows predominantly over lateral half was noted. Hair appeared short, lusterless, and brittle with profuse scaling over the scalp and eyebrows. Trichoscopy showed trichorrhexis nodosa, “golf-tee” hair, “bamboo” hair, and “matchstick” hair over eyebrows. Serum IgE levels were raised. Skin biopsy was suggestive of ILC. Diagnosis of NS was made. The first line of treatment is topical therapy with emollients, topical corticosteroids and calcineurin inhibitors, Narrow band- ultraviolet B (NB-UVB), and infliximab.